[PP.24.06] CARDIAC PHENOTYPE BASED ON ANGIOGRAPHIC SUBTYPES AND VASCULAR INVOLVEMENT IN PATIENTS WITH FIBROMUSCULAR DYSPLASIA –ARCADIA-POL STUDY. (September 2017) - Dobrowolski, P.; Warchol-celinska, E.; Klisiewicz, A.; Hanus, K.; Prejbisz, A.; Florczak, E.; Witowicz, H.; Aniszczuk, A.; Kowalczyk, K.; Ziebka, J.; Swiatlowski, L.; Falkowski, A.; et al.
Abstract : Objective: To evaluate echocardiographic morphology and function in patients with fibromuscular dysplasia (FMD) in relation to angiographic subtypes and vascular involvement of FMD. Design and method: 137 patients with FMD underwent whole body angio-CT. 117 patents (F-94, M-23) with renal FMD were divided according to type of FMD in renal arteries as: unifocal and multifocal groups. Left ventricular mass index (LVMI) was obtained by echocardiography. Systolic function was assessed by ejection fraction and global longitudinal strain (GLS). Diastolic function was measured by mitral flow parameters (A, E) and early diastolic myocardial velocity (E'). E/A, E/E' and E'/A' ratio were calculated. Results: Patients with multifocal FMD (n = 79) were older then patients with unifocal FMD (n = 38). There were no differences in blood pressure values as well as in LVMI and systolic function between analyzed groups (Table 1). There were significant differences in diastolic function between multifocal and unifocal groups (Table 1). After correcting for age or removing patients with significant renal arteries stenosis, the results remained still significant. There were no differences in echocardiographic parameters when patients were divided according to the number of vascular beds involved FMD. Figure. No caption available. Conclusions: Our study showed that patients with multifocal renal FMD differed in diastolic function parameters as compared to unifocal angiographic type. There were no differences in systolic function assessed by speckle tracking echocardiography method between analysed groups.